Validation of international classification of diseases 10th revision-based injury severity score (ICISS) in patients with motor vehicle injuries in Thailand, 1998 - Chansatitporn, Natkamol
The Injury Severity Score (ISS) has served as the standard measure of the injury severity. However, there is considerable time and expense involved in the collection of the information. The International Classification of Diseases 9th Revision-based Injury Severity Score (ICISS), a recently developed injury severity measure, has been demonstrated to be superior to ISS. Since ICISS was orginally developed based on ICD-9 revision, consequently, the validity of ICD-10-based ICISS should be verified.The purpose of this study was to compare the ability of ISS and ICISS as predictors of mortality and length of hospital stay (LOS) in motor vehicle injured patients as well as to develop the best model to predict mortality.The data were obtained from ther records of the Injury Surveillance system of the Ministry of Public Health, Thailand operating in twelve participant provincial hospitals during January 1 to 31 December 1998. The study subjects were adult inpatients aged 15 years and above with motor vehicle injuries. The bootstrap technique was performed for evaluating performance of ISS and ICISS. The ability of ISS and ICISS to predict mortality and length of hospital stay were compared with respect to the Bayesian Information Criterion (BIC) value. In addition, the accuracy of the ISS and ICISS model was assessed using sensitivity, specificity, accuracy and misclassification rates.A total of 13,604 patients were included in this analysis. The overall mortality was 5.11. The ICISS showed a better performance in predicting mortality than ISS. In contrast, the ICISS is a weaker predictor for length of hospital stay than the ISS. The accuracy of ICISS model demonstrated a slight improvement over that of the ISS model in predicting mortality.The ICISS methodology could be extended to ICD-10 horizon as a standard injury measure in the place of ISS for predicing mortality of motor vehicle injury in Thailand. However, because this is the first study to validate the ICISS methodology using database in Thailand, further investigations are needed to validate these findings.